1994
DOI: 10.1073/pnas.91.13.6108
|View full text |Cite
|
Sign up to set email alerts
|

par-2, a gene required for blastomere asymmetry in Caenorhabditis elegans, encodes zinc-finger and ATP-binding motifs.

Abstract: The par-2 gene of Caenorhabditi elgans functions in early embryogenesis to ensure an amme first cleavage and the segregation of cytoplasmic factors. Both processes appear to be required to generate daughter blastomeres with distinct developmental potential. We isolated an allele of par-2 by using a screen for maternal-effect lethal mutations in a strain known for its high frequency of transposition events. A transposable lement was found to be linked to this allele. Sequences lanig the site oftransposon insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…The lw32 allele contains a stop codon in the middle of the par-2 coding sequence and was shown to behave as a strong loss of function (Levitan et al 1994;Boyd et al 1996). We found that 99.4 6 0.3 75.2 6 3.9 spat-3(gk22) 99.8 6 0.0 98.7 6 0.1 rpn-10(tm1180) 99.0 6 0.1 99.2 6 0.3 rpn-10(tm1349) 99.0 6 0.2 97.3 6 0.8 nos-3(q650); par-2(it5ts) 86.5 6 2.0 53.6 6 1.6 nos-3(q650); par-2(lw32) 54.6 6 4.7 b ND par-2(it5ts); spat-3(gk22) 86.6 6 2.2 22.9 6 5.9 par-2(lw32); spat-3(gk22)…”
Section: Resultsmentioning
confidence: 99%
“…The lw32 allele contains a stop codon in the middle of the par-2 coding sequence and was shown to behave as a strong loss of function (Levitan et al 1994;Boyd et al 1996). We found that 99.4 6 0.3 75.2 6 3.9 spat-3(gk22) 99.8 6 0.0 98.7 6 0.1 rpn-10(tm1180) 99.0 6 0.1 99.2 6 0.3 rpn-10(tm1349) 99.0 6 0.2 97.3 6 0.8 nos-3(q650); par-2(it5ts) 86.5 6 2.0 53.6 6 1.6 nos-3(q650); par-2(lw32) 54.6 6 4.7 b ND par-2(it5ts); spat-3(gk22) 86.6 6 2.2 22.9 6 5.9 par-2(lw32); spat-3(gk22)…”
Section: Resultsmentioning
confidence: 99%
“…LGL-1 is sufficient to rescue PAR-2 loss of function par-2(lw32) is a strong allele that produces a truncated PAR-2 protein of a predicted 233 amino acids (Levitan et al, 1994) that lacks the domain required for cortical localization (Hao et al, 2006). If LGL-1 and PAR-2 function redundantly, we hypothesized that overexpression of LGL-1 might be sufficient to rescue the lethality of par-2(lw32).…”
Section: Overexpression Ofmentioning
confidence: 99%
“…The products of the Par genes are quite diverse in function. Par-1 and Par-4 encode serine/threonine-directed protein kinases Watts et al 2000); Par-2 is a RING finger domain protein that may function as an E3 ubiquitin ligase (Levitan et al 1994); Par-3 and Par-6 are PDZ (PSD95/Dlg/ZO1) domain-containing proteins with scaffolding or adaptor functions (Etemad-Moghadam et al 1995;Hung and Kemphues 1999); Par-5 is a 14-3-3 protein that binds to phosphorylated serine and threonine residues (Morton et al 2002); and PKC-3 is an atypical protein kinase C (aPKC). With the exception of Par-2, all of the Par proteins and aPKC are conserved throughout the Metazoa.…”
Section: Par Proteins: Interpreters Of Cell Polaritymentioning
confidence: 99%